Management Challenges for Business in Digital Economy: New Pathways and Research Trends - Korsakienė, Renata; Jesevičiūtė-Ufartienė, Laima; Vilkaitė-Vaitonė, Neringa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The digital economy has significantly impacted countries throughout the world by contributing to the growth of the economy and the further progress of societies. Recent developments demonstrate that the information and innovation-driven era triggered integration of traditional activities and digital technologies. Moreover, the rise of innovation has been accelerating in emerging industries such as cleantech, the new generation of information technology, biotechnology, and high-end equipment manufacturing. The estimations provided by the World Economic Forum predict that "new value creation over the next decade will be based on digitally enabled platform business models". Therefore, organizations must change the traditional approaches adopted and capture value in the context of digital disruptions. These tendencies raise a number of management challenges that need to be solved by the efforts of the scientific community. Therefore, this Special Issue provides the platform for a fruitful discussion and the development of relevant theories.